ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PENGGUNAAN PRODUK ARTIFICIAL INTELLIGENCE PADA VOICE ASSISTANT - Tobing, Ricardo Joynest; Zarlis, Muhammad (Universitas Multi Data Palembang, 2024)
Artificial intelligence technology is currently developing rapidly. This is caused by the need for users to innovate to help users in their daily activities, which of course is supported by the current internet network which is starting to be very adequate in various regions. The research currently being conducted aims to analyze and understand how the user experience is in using artificial intelligence technology, especially in voice assistant products, namely smarthome or smartspeaker. The data collection method used is through a questionnaire. Questionnaires will be distributed to 500 respondents in the DKI Jakarta area, who use voice assistants on smartphones, smarthomes or smartspeakers. The data that has been obtained is then processed using SmartPLS to analyze the validity and hypotheses that have been determined. The research model used is the UTAUT (Unified Theory of Acceptance and Use of Technology) model. The variables in this study are performance expectancy, effort expectancy, social influence, facilitating conditions, towards behavioral intention to use behavior in using voice assistants on smartphones, smarthomes or smartspeakers. This variable will measure the level of user product usage and what are the issues for users when using voice assistant products on smartphones, smarthomes or smartspeakers. The results of the data collected and analyzed in this study will show how acceptance from users of voice assistant products can help user activities, as well as what factors are obstacles for users in using voice assistants.